Effect of Nd: YAG laser irradiation to the temporomandibular joint on taste threshold - Hiroyasu Yamaguchi; Shiro Suzuki; Satoshi Beppu; Hozumi Watanabe; Satoshi Shirakawa; Akihiro Yashima; Takatoshi Nagano; Mohei Yuasa; Kazuyuki Kobayashi; Kazuhiro Gomi (Elsevier, 2021)
Background/purpose: The tissue absorption laser has been clinically applied to alleviate pain in various areas. It is used for pain relief from temporomandibular disease (TMD) in dentistry. Although the facial and trigeminal nerves are distributed around the temporomandibular joint, the effects of laser irradiation and absorption on the neural functions have not been directly studied. In this study, the Nd:YAG laser was applied to an area where the facial nerve passes with photonic radiation for the treatment of TMD. Materials and methods: Ten volunteers including seven males and three females were selected as subjects. Nd:YAG laser was irradiated area included several internal and external standard and associated acupuncture points. The chorda tympani nerve, a branch of facial nerve is distributed to the front two thirds of the tongue and is associated with the sense of taste. We evaluated the effect of laser irradiation and absorption on the taste function by means of an electric taste meter. Results: No significant difference was identified in the values between before and after laser irradiation (Wilcoxon signed-rank test). Conclusion: It was confirmed that there was no effect on taste function while applying Nd:YAG laser irradiation around the TMD joint.